2021
DOI: 10.3390/su13020932
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability and Waste Imports in China: Pollution Haven or Resources Hunting

Abstract: Motivations behind a country’s importation of waste are categorized into the pollution haven hypothesis (PHH) and the resource hunting hypothesis (RHH). The importation of wastes can lead to environmental sustainability concerns, requiring governments to intervene when the market fails to reduce the negative externalities by strengthening and implementing environmental regulations. Motivated by China’s position within a rapidly growing but environmentally damaging sector of trade, this paper has three goals: (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 35 publications
(90 reference statements)
3
8
0
Order By: Relevance
“…First, we constructed a quasi-natural experiment and empirically analyzed the impact of the NSP on the category, quantity, and price margins of Chinese imports for the first time. Second, we further confirm, based on Li et al [3], that the NSP mainly suppresses the motivation of developed economies to seek a "Pollution Haven" for exporting highly polluting waste to China but does not affect China's access to intermediate input resources from developing economies. Third, we discussed the heterogeneity in national environmental policies and demonstrated that the waste market of economies that actively implement product environmental impacts and encourage waste classification and recycling policies will not be significantly impacted.…”
Section: Introductionsupporting
confidence: 73%
See 4 more Smart Citations
“…First, we constructed a quasi-natural experiment and empirically analyzed the impact of the NSP on the category, quantity, and price margins of Chinese imports for the first time. Second, we further confirm, based on Li et al [3], that the NSP mainly suppresses the motivation of developed economies to seek a "Pollution Haven" for exporting highly polluting waste to China but does not affect China's access to intermediate input resources from developing economies. Third, we discussed the heterogeneity in national environmental policies and demonstrated that the waste market of economies that actively implement product environmental impacts and encourage waste classification and recycling policies will not be significantly impacted.…”
Section: Introductionsupporting
confidence: 73%
“…China's dominance is evident in its once over 50% share of global wastepaper and waste plastic imports, underscoring its pivotal role in the international waste recycling and reuse market [9]. Li et al [3] utilized a gravity model and panel data on 28 waste categories imported by China from 1995 to 2018 to analyze its drivers. Their findings suggest China's strategy to procure cost-effective intermediate goods from the global market, leading to substantial imports of scrap metal from developed nations and diverse waste types from developing countries.…”
Section: Global and Chinese Waste Import Motivationmentioning
confidence: 99%
See 3 more Smart Citations